Corruption, Development, and Deforestation: An Evidence From Southeast Asian Countries - Yusuf, Mochammad (KINERJA, 2023)
This study aims to analyze the determinants of deforestation in Southeast Asian Countries. The variables used in this research are economic growth, total population, foreign direct investment, and corruption index. This research uses secondary data obtained from the World Bank, Rainforest Mongabay, and Trading Economics with a time range of 2011-2020. The method used in this analysis is panel data regression. This research found that economic growth, total population, foreign direct investment, and corruption index are positive and significantly affect deforestation in Southeast Asia. This evidence became a concern for the government in responding to this, considering that deforestation is a phenomenon that cannot be ignored.